Nutritional status and survival of End-Stage Renal Disease patients treated with continuous ambulatory peritoneal dialysis - Shymova, A.; Shifris, I.; Dudar, I. (Ukrainian Journal of Nephrology and Dialysis, 2019)
The objective of the work was to study the survival peculiarities ofend-stage renal disease patients treated with continuous ambulatory peritoneal dialysis (CAPD) depending on the nutritional status and informative markers associated with it. Methods. 105 ESRD patients who received CAPD treatment during 2012 - 2017 years at the Kyiv Scientific and Practical Center of Nephrology and Dialysis, which is the clinical base of the State Institution "Institute of Nephrology National Academy of Medical Sciences of Ukraine" were included in the cohort prospective open study. The survival analysis was carried out both in the studied population as a whole and in groups depending on the nutritional status (NS) indicators defined basing on the calculation of the subjective global assessment (SGA) points: the first group (n = 51) consisted of patients without malnutrition, the second group (n = 30) - patients with a mild degree of malnutrition, the third group (n = 13) - patients with a moderate degree of malnutrition, and the fourth group (n = 11) - patients with a severe degree of malnutrition. The survival analysis was conducted both in the groups in compliance with NS, and depending on the informational markers associated with NS, in particular, albumin, body mass index (BMI), residual renal function (RRF). Survival were calculated using the Kaplan-Meier method, and the difference between survival rates was analyzed using the log-rank test and χ². The starting date of peritoneal dialysis treatment was considered as the starting point of the monitoring. The difference was considered to be accurate at p <0.05. Analyzed cases were included till January 7, 2019. The event risk assessment was carried out with the probability of relative risk (RR) values calculating their confidence intervals (95% CI). Results.Forty-three (40.95%) patients died during the current analysis, 17 patients were switched to the hemodialysis (HD), 4 patients had undergone kidney transplantations. Cardiovascular disease was the leading cause of death (41.9%), the second cause of death by frequency was bacterial infections (20.9%). Longer monitoring periods death rate was significantly higher in patients of group with an average (11/84.6% vs 14/27.45%, p <0.0001; RR - 3.08; 95% CI: 1.8 -5.09)and a mild degree of nutritional disorders (ND) (11/84.6% vs 11/36.7%, p = 0.0018, RR - 2.3, 95% CI: 1.36-3.89) compared with normal NS.Similarly, the percentage of died patients with a severe ND degree was significantly higher than those with a normal nutritional status (7/63.6% vs. 14/27.45%, p = 0.0091, RR - 2.31, 95% CI: 1.23 - 4.35). The cumulative survival during the 1- year amounted to 90% of patients for 3 and 5 years - 64% and 41%, respectively. It was found that the survival rate of PD patients is credibly higher in groups with normal NS ormild ND degree than patients of group with a moderate or severe degree of nutritional disorders (χ2 = 22,9; df = 3; p = 0,00004). The cumulative survival for 1 and 3 years was 97%, 98%, 70%, 81% and 76%, 70%, 24%, 36% in groups of patients without nutritional disorder, with mild nutritional disorders, moderate and severe disorders, respectively. The cumulative survival with serum albumin level <35 g/l and ≥ 35 g/l in 1 and 3 years was 73% vs 96% and 37% vs 74%, respectively (p = 0.00005, log-rank test). Similarly, the proportion of survivors with BMI > 24 kg/m2 was apparently higher than those with an indicatorBMI ≤ 24 kg/m2, and it was in 1 and 3 years 94% vs 86% and 79% vs 47%, respectively (p = 0.00321, log-rank test). Veritable differences have been registered in the cumulative frequencies of survivors depending on RRF value: the survival rate was significantly higher among patients with RRF ≥ 5 ml/min/1.73 m² and significantly lower among patients with RRF <2 ml/min/1.73 m2 (χ² = 17.4; df = 2; p = 0.00016). Conclusions.Thus, our studyfound that serum albumin level, BMI and RRF magnitude are the markers for the survival of ESRD patientstreated with PD. Veritable difference between the survival of patients depending on the nutritional status was stated. Three-year cumulative survival with mild degree of malnutrition group was twice as high as in severe nutritional disorders and it was 70% vs 36% (p <0.001). The relative risk of death from all causes increases by 3.1 and 2.32 times for moderate and severe nutritional disorders patients compared to the patients group with normal NS.